Effects of Baduanjin on postoperative rehabilitation of patients with breast cancer: A protocol for systematic review and meta-analysis. Issue 17 (30th April 2021) - Chen, Guangyan; Lin, Yuqin; Zhao, Xiyun; Pu, Bin
Abstract: Background: Baduanjin, as an ancient Chinese exercise, is beneficial to both physical and mental health. Moreover, researchers discovered that Baduanjin has effects on the recovery of postoperative breast cancer patients. Yet, nobody focused on the systematic review, which can provide convincing evidence to verify the effect of Baduanjin in breast cancer patients. Therefore, our study will conduct a systematic review to fill in the blank, besides we will offer new evidence for clinical workers. Methods: PubMed, Embase.com, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and SinoMed will be used for literature search, retrieve time is up to June 1, 2021. We will include randomized controlled trials that evaluate the effects of Baduanjin on postoperative rehabilitation for breast cancer patients. Two independent researchers will perform study selection and data extraction. The risk of bias will be assessed by the Cochrane bias assessment tool. We will use funnel plot and Egger test to evaluate publication bias. Stata 13.0, as a necessary software, will be used to perform statistical analysis. Also, we will utilize subgroup analyses and sensitivity analyses to explore the sources of heterogeneity. Results: The results of this study will be published in a peer-reviewed journal. Conclusion: Evidence that adequately assesses the effect of Baduanjin in the recovery of breast cancer patients will be confirmed through this systematic review. Our study will offer a guideline for clinical workers, besides we will supply a new way for the rehabilitation of breast cancer patients.